IMPROVING STUDENTS' WRITING SKILL IN ARGUMENTATIVE TEXT THROUGH PICTURE WORD INDUCTIVE MODEL (PWIM) AT TWELVE GRADE OF SMA NEGERI 4 PEMATANGSIANTAR - Juni Sari Sianturi; Aulia Monica Tambunan; Elisabeth Dwi Clara; Daniel Binsah Lumbangaol; Dumaris Elseria Silalahi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This study aimed to investigate the effectiveness of the Picture Word Inductive Model(PWIM) in improving students’ writing skills in argumentative texts at the twelfth grade ofSMA Negeri 4 Pematangsiantar. The study was conducted in response to students’ difficultiesin generating ideas, organizing arguments coherently, and applying appropriate grammaticalstructures in argumentative writing. The Picture Word Inductive Model was implemented as aninstructional strategy to help students develop vocabulary, construct ideas systematically, andimprove their writing organization through visual stimuli. This research employed aquantitative approach using a quasi-experimental design involving two groups: class XII-6 asthe experimental group taught using the Picture Word Inductive Model and class XII-8 as thecontrol group taught using conventional teaching methods. Data were collected through pretestand post-test writing tasks assessed using an analytical scoring rubric covering content,organization, vocabulary, language use, and mechanics. The findings revealed that the meanscore of the experimental group increased significantly from 51.39 in the pre-test to 74.58 inthe post-test, while the control group showed a smaller improvement from 54.17 to 65.97. Theresult of the t-test analysis showed that the obtained t-value (12.88) was higher than the t-tablevalue (1.99) at the 0.05 significance level, indicating a statistically significant differencebetween the two groups. These findings suggest that the Picture Word Inductive Modeleffectively improves students’ argumentative writing skills by enhancing idea development,vocabulary mastery, and text organization. Therefore, PWIM can be considered an effectiveinstructional model for teaching argumentative writing in EFL classrooms.Keywords: Writing skills; Argumentative text; Picture Word Inductive Model; EFL learning;quasi-experimental research